ADELMAN, Miriam et al. (Org). Mulheres, homens, olhares e cenas. - Oliveira, Ana Claudia Delfini Capistrano de (Revista Estudos Feministas, 2012)
ADELMAN, Miriam et al. (Org). Mulheres, homens, olhares e cenas.